2011
DOI: 10.1124/dmd.111.040766
|View full text |Cite
|
Sign up to set email alerts
|

Species Differences in Distribution and Prediction of HumanVssfrom Preclinical Data

Abstract: ABSTRACT:Prediction of human volume of distribution at steady state (V ss ) before first administration of a new drug candidate to humans has become an important part of the drug development process. This study examines the assumptions behind interspecies scaling techniques used to predict human V ss from preclinical data, namely the equivalency of V ss,u and/or f ut across species. In addition, several interspecies scaling techniques are evaluated side by side using a set of 67 reference compounds where obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 37 publications
3
46
0
Order By: Relevance
“…1, the rat, dog, and human hepatocyte relay method gave good prediction of in vivo intrinsic clearance [additional human data were collected during this study and added to the previously published set (Di et al, 2012)]. For most compounds, 9.0 6 3.9 1.2 Antipyrine 14 (Balani et al, 2002) 14 6 1.4 1.0 Naproxen 22 c (Suh et al, 1997) 20 6 3.0 1.1 (6)-Ketoprofen 48 -114 d (Granero and Amidon, 2008;Neirinckx et al, 2011) 24 6 1.2 2.0-4.7 e a F u and R b values were from the literature (Berry et al, 2011) or in-house data. b The equation CL iv = oral dose (Dose PO )/oral area under the curve (AUC PO ) Â F was used to derive i.v.…”
Section: Discussionmentioning
confidence: 99%
“…1, the rat, dog, and human hepatocyte relay method gave good prediction of in vivo intrinsic clearance [additional human data were collected during this study and added to the previously published set (Di et al, 2012)]. For most compounds, 9.0 6 3.9 1.2 Antipyrine 14 (Balani et al, 2002) 14 6 1.4 1.0 Naproxen 22 c (Suh et al, 1997) 20 6 3.0 1.1 (6)-Ketoprofen 48 -114 d (Granero and Amidon, 2008;Neirinckx et al, 2011) 24 6 1.2 2.0-4.7 e a F u and R b values were from the literature (Berry et al, 2011) or in-house data. b The equation CL iv = oral dose (Dose PO )/oral area under the curve (AUC PO ) Â F was used to derive i.v.…”
Section: Discussionmentioning
confidence: 99%
“…3) Does correction of plasma protein binding yield better or worse estimation of human VD? Depending on the animals used in the experiments, the diversity of the compounds, and the number of the compounds in the studies, the conclusions can be different (Obach, 1997;Ward and Smith, 2004;Obach, 2007;Hosea et al, 2009;Sui et al, 2010;Berry et al, 2011;Jones et al, 2011b). A recent study with a large set of well-characterized, structurally diverse compounds concluded that monkey was superior to dog or/and rat in all the methods tested, presumably because monkey is evolutionarily closest to human (Lombardo et al, 2013b).…”
Section: Predicting Volume Of Distributionmentioning
confidence: 99%
“…Prediction of human VD from in vitro tissue binding data has been reported over several years (Obach, 2007;Berry et al, 2011;Berezhkovskiy, 2012). The assumption is that in vitro surrogate measurements of tissue homogenate binding are representative of in vivo tissue binding.…”
Section: Predicting Volume Of Distributionmentioning
confidence: 99%
See 2 more Smart Citations